Preparedness for self-isolation or quarantine and lockdown in South Africa: results from a rapid online survey - Sibusiso Sifunda; Tholang Mokhele; Thabang Manyaapelo; Natisha Dukhi; Ronel Sewpaul; Whadi-Ah Parker; Saahier Parker; Inbarani Naidoo; Sean Jooste; Shandir Ramlagan; Razia Gaida; Musawenkosi Mabaso; et al. (BMC, 2021)
Abstract Background The World Health Organization (WHO) declared the COVID-19 pandemic a public health emergency of international concern. South Africa, like many other countries, initiated a multifaceted national response to the pandemic. Self-isolation and quarantine are essential components of the public health response in the country. This paper examined perceptions and preparedness for self-isolation or quarantine during the initial phase of the pandemic in South Africa. Methods The analysis used data obtained from an online quantitative survey conducted in all nine provinces using a data-free platform. Descriptive statistics and multivariable logistic regression models were used to analyse the data. Results Of 55,823 respondents, 40.1% reported that they may end up in self-isolation or quarantine, 32.6% did not think that they would and 27.4% were unsure. Preparedness for self-isolation or quarantine was 59.0% for self, 53.8% for child and 59.9% for elderly. The odds of perceived possibility for self-isolation or quarantine were significantly higher among Coloureds, Whites, and Indians/Asians than Black Africans, and among those with moderate or high self-perceived risk of contracting COVID-19 than those with low risk perception. The odds were significantly lower among older age groups than those aged 18-29 years, and those unemployed than fully employed. The odds of preparedness for self-isolation or quarantine were significantly less likely among females than males. Preparedness for self, child and elderly isolation or quarantine was significantly more likely among other population groups than Black Africans and among older age groups than those aged 18-29 years. Preparedness for self, child and elderly isolation or quarantine was significantly less likely among those self-employed than fully employed and those residing in informal dwellings than formal dwellings. In addition, preparedness for self-isolation or quarantine was significantly less likely among those with moderate and high self-perceived risk of contracting COVID-19 than low risk perception. Conclusion The findings highlight the challenge of implementing self-isolation or quarantine in a country with different and unique social contexts. There is a need for public awareness regarding the importance of self-isolation or quarantine as well as counter measures against contextual factors inhibiting this intervention, especially in impoverished communities.